Using 3D printed formworks for the creation of steel fibre reinforced concrete-plastic columns. (27th June 2022) - Katzer, Jacek; Skoratko, Aneta
Highlights: Traditional formworks for columns are limited in regards of their cross-sections. Authors propose a 3-D printed plastic stay-in-place-formworks with fractal based cross-sections. 3-D printed plastic formworks also play the role of reinforcement. After hardening a 3-D printed formwork and concrete form one composite element. Created elements are characterized by significant compressive strength and quasi-plastic load–strain behaviour. Abstract: A concept of steel fibre reinforced concrete–plastic columns was proved and discussed in the paper. Plastic was playing the role of stay-in-place 3D printed formwork. Seven cross-sections representing different types of shapes of columns (from circular to fractal-based) were created. 3D printed plastic stay-in-place formworks were filled with steel fibre reinforced concrete. After ordinary curing, the specimens were loaded. During the tests load–strain characteristics were recorded. Both the destruction characteristics and the energy dissipated during the loading up to 3.5% strain were of special interest. The achieved results were analysed and discussed. Columns with traditional circular and square cross-section were characterized by sudden destruction of the formworks. Specimens with fractal-based cross-sections were characterized by a very smooth destruction process associated with significant deformations of formworks. All steel fibre reinforced concrete–plastic columns in question were characterized by highly quasi-plastic behaviour. The achieved results proved that it is feasible to replace traditional formwork and ordinary concrete (reinforced by steel bars and stirrups) by much more automatized 3D printing of plastic and steel fibre reinforced concrete based solution. The future aims of the much needed research should cover both large scale column specimens and other structural elements.